Faktor-faktor yang mempengaruhi minat masyarakat mengajukan kredit di Financial Technology - Zulkarnaini; Aulia; Early Ridho Kismawadi (FEBI IAIN Langsa, 2020)
The purpose of this study was to find out how ease of use, effectiveness and risk affected people’s interest in applying for dibfintech loans. The type of research used is quantitative. Data collection techniques used were questionnaires. The population in this study is the entire community in the district of Aceh Tamiang. The sampling technique used was a quota sampling technique with a total of 75 people. Data analysis techniques using the classic assumption test, multiple linear regression test, hypothesis testing and coefficient of determination test. The results showed that partial ease of use had a positive and significant effect on people’s interest in applying for credit at fintech with a value of t arithmetic 2,506 > 1,993 (t table) and sig value 0,003 < 0,05. Partially the effectiveness is positive and significant effect on people’s interest in applying for credit in fintech with a calculated exchange rate of 3,603 > 1,993 (t table) and a sig value of 0,002 < 0,05. Partially the risk of positive and significant effect on people’s interest in applying for credit in fintech with a value of t arithmetic 2,296 > 1,993 ( t table) and a sig value of 0,004 < 0,05. Simultaneously the ease of use, effectiveness and risk have a positive and significant impact on people’s interest in applying for credit at fintech. This is evidenced by the calculated F value > F table (4,192 > 3,12)